Does Microfinance Cause or Reduce Suicides? Policy Recommendations for Reducing Borrower Stress1. (March 2015) - Ashta, Arvind; Khan, Saleh; Otto, Philipp
<x xml:space="preserve">Abstract</x> Male suicides seem to accompany microfinance growth and penetration.